Jewish histories of the Holocaust : new transnational approaches - Goda, Norman J. W., 1961-; Bartov, Omer (Making sense of history ;, 2014)
For many years, histories of the Holocaust focused on its perpetrators, and only recently have more scholars begun to consider in detail the experiences of victims and survivors, as well as the documents they left behind. This volume contains new research from internationally established scholars. It provides an introduction to and overview of Jewish narratives of the Holocaust. The essays include new considerations of sources ranging from diaries and oral testimony to the hidden Oyneg Shabbes archive of the Warsaw Ghetto; arguments regarding Jewish narratives and how they fit into the larger fields of Holocaust and Genocide studies; and new assessments of Jewish responses to mass murder ranging from ghetto leadership to resistance and memory.